The effect of water immersion delivery on the strength of pelvic floor muscle and pelvic floor disorders during postpartum period: An experimental study. Issue 41 (October 2017) - Zhao, Yun; Xiao, Mei; Tang, Fei; Tang, Wan; Yin, Heng; Sun, Guo-Qiang; Lin, Yin; Zhou, Yong; Luo, Yan; Li, Lu-Man; Tan, Zhi-Hua
Abstract: Background: Water immersion delivery is a non-pharmacological approach to ease labor pain. This paper aims to investigate the effect of water immersion delivery on increasing strength of pelvic floor muscle (PFM) and relieving pelvic floor disorders (PFDs) during postpartum period. Methods: A total of 2749 vaginal-delivery primiparas in postpartum 6-8 weeks were selected as research objects. Based on the modes of delivery, 600 patients were assigned into water immersion delivery group, 2149 were assigned into conventional delivery group. The scales of PFM strength and pelvic organ prolapsed (POP) were determined by specially trained personnel using digital palpation, and the symptoms of stress urinary incontinence (SUI) were investigated by questionnaire survey. The weak PFM strength was improved by doing Kegel exercise at home for 6-8 weeks. Results: We found that ①The rate of episiotomy in water immersion delivery group was 77.50% (465/600), which was lower than that in conventional delivery group (84.69%, 1820/2149) ( P  < .01); The primiparas without having an episiotomy have higher PFM strength than those having an episiotomy for both groups ( P  < .01). ②There was a negative correlation between the scale of PFM strength and SUI or POP, wherein the r-values were −0.135 and −0.435, respectively ( P  < .01). ③The rate of SUI was 6.50% (39/600) in water immersion delivery group and 6.89% (148/2149) in the conventional delivery group, wherein the intergroup difference was not significant ( P  > .05); ④The rates of vaginal wall prolapsed and uterus prolapsed were 29.83% (179/600) and 2.83% (17/600) in water immersion delivery group and 30.95% (665/2149) and 4.37% (94/2149) in the conventional delivery group, wherein the intergroup difference was not significant ( P  > .05). ⑤After Kegel exercise, the strength of PFM was promoted ( P  < .01). Conclusion: Water immersion delivery has been proved to a beneficial alternative method for conventional delivery method. This delivery mode is associated with fewer episiotomy rate, and avoiding episiotomy is beneficial for maintaining PFM strength of women in postpartum 6-8 weeks. The strength of PFM during postpartum period can be improved by doing Kegel exercise at home.